Natural resources and decentralization in Nicaragua: are local government up to the job? - Larson, A.M. (2002)
Both decentralization and natural resource management literature suggest that natural resources could benefit from the redistribution of centralized management authority. Yet, neither has sufficiently examined the processes already underway in numerous developing countries to decentralize resource management from central to municipal government authorities. This study reviews the role of 21 local governments in forest management in Nicaragua. It finds that most interventions are economically motivated, and that three key factors are needed for local governments to be good resource managers: capacity, incentive and long-term commitment. These three factors are part of a process in which civil society can play a critical role.